Wireless Sensor Network for Soil Monitoring - Guico, Maria Leonora (Archīum Ateneo, 2019)
This Wireless Sensor Network (WSN) for Soil Monitoring is a system consisting of nodes with sensors and telemetry capabilities. This system is meant for deployment in agricultural applications, specifically, in banana plantations affected and unaffected by Fusarium oxysporum f. sp. cubense Tropical Race 4 (TR4). We focused on monitoring soil parameters such as pH, temperature and moisture. Other environmental parameters such as air temperature, air humidity and ambient light were gathered. Each sensor node uses a GSM data-transmission module for more stable and robust method even in far-flung areas in the Philippines. Raw data from the sensor nodes are stored in a web server for processing and data visualization. Reliability of daily transmission is 87.28%.